The relationship between science and government in Iran: a historical perspective - Shamsaie, Maryam; Abdul Murad, Mohd Hazim Shah (Leena and Luna International, 2013)
Researchers here at this point to define the relationship between the government actions and the process of scientific activities. It can be also narrated in this way: How do politician’s attitudes, policies and decisions impact the scientific arena? In common wisdom, the functions of science and thinking in a closed society with a closed government is absolutely affected and is therefore canalized in the best case and even nonexistent as a result of suppression of free, independent thoughts in the worst scenario. In this paper we shall look at the relationship between Islam, science and government in Iran from a historical perspective. We will shall by looking at science in Iran in the ancient (pre-Islamic) period, in the Middle Age after the advent of Islam, and finally in the modern period.